2015
DOI: 10.1890/ehs15-0003.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling vulnerability of protected areas to invasion by chromolaena odorata under current and future climates

Abstract: Invasive plant species and climate change are among the biggest threats to the ecological integrity of many ecosystems, including those of protected areas. Effective management of invasive plants requires information regarding their spatial distributions. Using maximum entropy, we modeled habitat suitability for an invasive plant species Chromolaena odorata under current and future climatic conditions (HadGEM2-ES and MIROC5) in protected areas of four West African countries (Benin, Côte d'Ivoire, Ghana, and To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 31 publications
1
39
0
2
Order By: Relevance
“…, Fandohan et al. ). The ecological effects of C. odorata establishment on soil nutrient levels have been reported in several studies conducted in Africa (e.g., Kanmegne et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…, Fandohan et al. ). The ecological effects of C. odorata establishment on soil nutrient levels have been reported in several studies conducted in Africa (e.g., Kanmegne et al.…”
Section: Introductionmentioning
confidence: 99%
“…A previous modeling study suggested that humid climates are preferable for the establishment and growth of C. odorata and that broad tropical humid regions, particularly those with latitudes lower than 9°30′ to 10° N, are projected to be suitable habitats for C. odorata under future climate conditions (Fandohan et al. ). While Mediterranean, semi‐arid, and temperate climates are considered safe from invasion (Kriticos et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The "10 percentile training presence" corresponds to the logistic probability above which, when sampled to grid values, the 10% least suitable presence points cannot fall. This threshold classified fairly the continuous maps for our studied species, and it also was used by Fandohan et al (2015). The model used for the classification was the average of the ones that came from the bootstrapping sampling with 10 replications.…”
Section: Spatial Analysis and Decisionmentioning
confidence: 99%